1998
DOI: 10.1159/000054323
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bacterial Endotoxin on in vivo Pulsatile Gonadotropin Secretion in Adult Male Rats

Abstract: Immune system disorders are often accompanied by alterations in the reproductive axis. The bacterial endotoxin (lipopolysaccharide or LPS) has central inflammatory effects, and activates cytokine release (immune system mediatory factors) in the hypothalamus, where the luteinizing hormone-releasing hormone neurons are located. The present study was designed to investigate the effect of LPS on the pulsatile release of LH and FSH in adult male rats. With this aim, orchidectomized male rats were implanted with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 30 publications
1
35
0
1
Order By: Relevance
“…Other studies performed on ovariectomized ewes showed that endotoxin suppressed GnRH pulsatile release into hypophyseal portal blood (Battaglia et al, 1997). Furthermore, it was previously demonstrated in rats that LPS also suppressed the pulsatile LH secretion pattern (Refojo et al, 1998). This suggests that inhibition of reproduction processes during immune stress occurs in a large part at the hypothalamic level, however, it cannot be excluded that it also results from processes occurring directly at the pituitary level.…”
Section: Discussionmentioning
confidence: 97%
“…Other studies performed on ovariectomized ewes showed that endotoxin suppressed GnRH pulsatile release into hypophyseal portal blood (Battaglia et al, 1997). Furthermore, it was previously demonstrated in rats that LPS also suppressed the pulsatile LH secretion pattern (Refojo et al, 1998). This suggests that inhibition of reproduction processes during immune stress occurs in a large part at the hypothalamic level, however, it cannot be excluded that it also results from processes occurring directly at the pituitary level.…”
Section: Discussionmentioning
confidence: 97%
“…These data confirm our previous observation that IL-1 plays a role in the control of the production of these important testicular regulators (Okuma et al 2005), and further indicate that other components of the inflammatory cascade also must be involved. FSH, acting through its intermediate cAMP, reverses the effects of inflammation on activin A, which has important implications in vivo since serum FSH levels are directly inhibited by systemic inflammation as well (Refojo et al 1998). The observation that these regulatory responses occur in Sertoli cells from both adult and immature rats indicates that these responses are a property of the mature testis.…”
Section: Discussionmentioning
confidence: 99%
“…Each dam was administered 0.1 ml/100 g saline or LPS solution. The LPS dose chosen was based on a study by Refojo et al [25] , who showed that 200 and 250 g/ kg LPS decreased the release rates of luteinizing hormone (LH) and follicle-stimulating hormone and suggested that gonadotropin-releasing hormone (GnRH) levels in the milk also decreased. In addition, this dose was reported to induce sickness behavior and fever in rats [36] .…”
Section: Treatmentmentioning
confidence: 99%
“…It has been hypothesized that prenatal stress disrupts the normal maternal hormonal milieu and suppresses the fetal testosterone peak on gestational days (GD) 18 and 19, a peak necessary for later expression and maintenance of male sexual behavior [3,24] . In addition, the critical period for the organizational actions of the gonadal hormones on the sexual differentiation of the rat brain extends from approximately the last week of prenatal life through the first postnatal week [23,25,26] . Thus, sexual behavior programming is controlled by the presence or absence of the appropriate hormones and various central neurotransmitters in the prenatal and postnatal periods [16,26,27] .…”
Section: Introductionmentioning
confidence: 99%